Changes in Body Mass Index and Atherosclerotic Disease Risk Score After Switching From Tenofovir Disoproxil Fumarate to Tenofovir Alafenamide. (4th October 2019) - Schafer, Jason J; Sassa, Kaitlin N; O'Connor, Jaclyn R; Shimada, Ayako; Keith, Scott W; DeSimone, Joseph A
Abstract: Background: Switching from tenofovir disoproxil fumarate (TDF) to tenofovir alafenamide (TAF)-containing antiretroviral therapy (ART) can improve renal function and bone mineral density in people with human immunodeficiency virus (PWH). The switch can also negatively influence cholesterol, but changes in body mass index (BMI) and atherosclerotic cardiovascular disease (ASCVD) risk are unknown. Methods: This retrospective observational study evaluated BMI and ASCVD risk score changes in virologically suppressed PWH who switched from TDF to TAF without switching other ART regimen components. Adults on TDF for ≥1 year with 2 consecutive HIV ribonucleic acid values <200 copies/mL before a TAF switch were included. Body weight, BMI, cholesterol, and ASCVD risk score were collected for the year before and after the switch. Pre- and postswitch values were compared with the Wilcoxon signed-rank test. Changes in BMI and ASCVD scores were modeled using generalized estimating equations regression. Results: One hundred ten patients were included. In unadjusted analyses, there were significant increases in weight, BMI, total cholesterol, LDL, HDL, and ASCVD risk score in the year after switching from TDF to TAF (each P ≤ .01). In regression models, switching from TDF to TAF was associated with a 0.45 kg/m 2 increase in BMI (95% confidence interval [CI], 0.14–0.76) and a 13% increase in ASCVD risk score (95% CI, 4%–23%). Conclusions: We observed significant BMI and ASCVD score increases in PWH 1 year after switching from TDF to TAF. The mechanism of changes is unclear and requires additional study. Abstract : This study evaluated virologically suppressed patients with HIV infection who switched from TDF to TAF, without switching other ART regimen components, and found significant increases in body mass index and atherosclerotic cardiovascular disease risk score.